PERBANDINGAN KONSTITUSI EKONOMI INDONESIA SEBELUM REFORMASI DAN PASCA REFORMASI - yauma tertibi, yauma tertibi (Universitas Nahdlatul Ulama Blitar, 2021)
Comparison results between the economic constitution in the 1945 Constitution before the amendment and the 1945 Constitution after the amendment, especially article 33 are as follows: 1. Whereas Article 33 paragraphs 1, 2 and 3 remain redacted, and this shows that this country remains as strong as possible against the socialist economic system which is more heavy for government, prioritizes common interests rather than individual interests, there is state ownership of production branches that are important and affect the livelihood of many people, there is an economy that is based on kinship. 2. Whereas paragraph 4 of Article 33 of the 1945 Constitution as a result of the amendments has created a new trend in the Indonesian economy, from previously purely socialist to a mixture of socialists and liberalists, in which the principles of efficiency which are characteristic of a liberalist economy are recognized and included in the economic system We. So that it opens more opportunities for liberal and neoliberal economic practices in the laws and regulations below. This of course can mean both good and bad, however no system is perfect, there are always advantages and disadvantages. It is our duty to maximize the advantages and try as much as possible to minimize the negative effects. Because it has been decided in our Constitution, so we must of course be able to mean both good and bad, however no system is perfect, there are always advantages and disadvantages. It is our duty to maximize the advantages and try as much as possible to minimize the negative effects. Because it has been decided in our Constitution, we must implement it properly. And if we feel there are deficiencies in the system we choose, then we can initiate changes in our economic system. We propose changes to our basic economic policies in the constitution according to the procedure in Article 37 of the 1945 Constitution.